2006
DOI: 10.1128/aem.72.3.2031-2042.2006
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofVibrio parahaemolyticusin Shellfish by Use of Multiplexed Real-Time PCR with TaqMan Fluorescent Probes

Abstract: We developed a multiplexed real-time PCR assay using four sets of gene-specific oligonucleotide primers and four TaqMan probes labeled with four different fluorophores in a single reaction for detection of total and pathogenic Vibrio parahaemolyticus, including the pandemic O3:K6 serotype in oysters. V. parahaemolyticus has been associated with outbreaks of food-borne gastroenteritis caused by the consumption of raw or undercooked seafood and therefore is a concern to the seafood industry and consumers. We sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 50 publications
3
84
1
2
Order By: Relevance
“…However, this assay may not be useful for the detection of pandemic strains that are devoid of orf8. Pyrolysis metastable atom bombardment mass spectrometry was shown to identify various phenotypic characteristics of V. parahaemolyticus (96). By targeting specific phenotypic markers, this technique may differentiate pandemic and nonpandemic V. parahaemolyticus strains.…”
Section: Methods For Detectionmentioning
confidence: 99%
“…However, this assay may not be useful for the detection of pandemic strains that are devoid of orf8. Pyrolysis metastable atom bombardment mass spectrometry was shown to identify various phenotypic characteristics of V. parahaemolyticus (96). By targeting specific phenotypic markers, this technique may differentiate pandemic and nonpandemic V. parahaemolyticus strains.…”
Section: Methods For Detectionmentioning
confidence: 99%
“…This could also be the reason why the detection rate of pathogenic V. parahaemolyticus with the trh gene in the environment is low. Ward and Bej used a multiplexed real-time PCR to detect V. parahaemolyticus in oysters, with results that were 51% positive for the tlh gene and 12.1% for the tdh gene but negative for the trh gene (45). In the study conducted by Rizvi and Bej, their results showed that 58% of the 24 oysters tested were positive for the tlh gene, 21% for the tdh gene, and 0.7% for the trh gene (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the reaction with amounts of V. rotiferianus DNA 10 times higher than that of V. harveyi DNA, V. harveyi were out of range from less than 1% of the initial amounts. Ward and Bej 16) reported that co-existence of >2,500-fold nonspecific DNA caused a coprecipitation effect and inhibited the PCR in the real-time PCR system for V. parahaemolyticus targeting tlh, ORF8, tdh, and trh genes. However, in this experiment, we did not use such a huge amount of DNA as the competitor.…”
mentioning
confidence: 99%